Idealism and freedom: Essays on Kant's theoritical and practical philosophy - Allison, Henry (Cambridge MIT Press, 1996)
Henry Allison is one of the foremost interpreters of the philosophy of Kant. This new volume collects all his recent essays on Kant's theoretical and practical philosophy. Special features of the collection are: a detailed defense of the author's interpretation of transcendental idealism; a consideration of the Transcendental Deduction and some other recent interpretations thereof; further elaborations of the tensions between various aspects of Kant's conception of freedom and of the complex role of this conception within Kant's moral philosophy.